Adsorpsi Logam Seng (Zn) Menggunakan Precipitated Calcium Carbonate (PCC) Dari Limbah Cangkang Kerang Lokan (Geloina expansa) - Rahayu, Helda Sri; Elystia, Shinta; Azis, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zinc (Zn) was a heavy metal that has a high toxicity and the presencein water or wastewater could be derived from industrial activitiesand activities of households. One of technology that can be applied to set aside Zn metals in wastewater wasadsorption method using PCC (precipitated Calcium Carbonate) of waste shells seashell. Zn metal concentrations were analyzed using instruments Atomic Absorption Spectrophotometer (AAS). This research aims to study the PCC capabilities in designated metal Zn in the variation of the mass of adsorbent 1; 2;3 and 4 grams, pH 4; 6 and 8 and a contact time of 15; 30; 45 and 60 minutes. The results showed the highest removal efficiency of Zn occurs at pH 6, and 3 grams of adsorbent mass contact time of 30 minutes with an efficiency of 99.058%. While the lowest efficiency at pH 4, the mass of adsorbent 3 grams and 15 minutes contact time with an efficiency of 1.533%. The adsorption process was assumed that the type of adsorption isotherms obtained is Langmuir isotherm assumed monolayer coating formed with R2 values of 0.541 and the value of adsorption capacity is 7.274 mg Zn / g PCC.. The results of XRD analysis showedthat the crystal structure of the PCC (CaCO3) after adsorption shaped calcite are seen from a row of intensity of diffraction peaks with 2 values similar to standard CaCO3 ICDD 01-076-2713.Keywords:adsorption,PCC lokan calm shell, adsorbent mass, pH, contact time, Zn.